2023
DOI: 10.1038/s41524-022-00949-7
|View full text |Cite
|
Sign up to set email alerts
|

nNPipe: a neural network pipeline for automated analysis of morphologically diverse catalyst systems

Abstract: We describe nNPipe for the automated analysis of morphologically diverse catalyst materials. Automated imaging routines and direct-electron detectors have enabled the collection of large data stacks over a wide range of sample positions at high temporal resolution. Simultaneously, traditional image analysis approaches are slow and hence unsuitable for large data stacks and consequently, researchers have progressively turned towards machine learning and deep learning approaches. Previous studies often detail wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…74 Similarly, Lee et al reported a deep learning-based technique to visualize single-atom defects in high-angle annular dark-field (HAADF)-STEM images of 2D monolayers down to the picometer scale and mapped the strain field induced by such defects. 75 Therefore, ML models are powerful tools to extract structural and chemical features that can provide insights about physical properties, [76][77][78][79][80] and they are able to identify relationships in huge datasets to extract useful information without explicitly fitting the data using complex equations.…”
Section: Introductionmentioning
confidence: 99%
“…74 Similarly, Lee et al reported a deep learning-based technique to visualize single-atom defects in high-angle annular dark-field (HAADF)-STEM images of 2D monolayers down to the picometer scale and mapped the strain field induced by such defects. 75 Therefore, ML models are powerful tools to extract structural and chemical features that can provide insights about physical properties, [76][77][78][79][80] and they are able to identify relationships in huge datasets to extract useful information without explicitly fitting the data using complex equations.…”
Section: Introductionmentioning
confidence: 99%